GERMAN PRISONERS OF WAR IN SOVIET CAMPS DURING WORLD WAR II: POLITICAL ASPECTS AND EVERYDAY REALITY (Journal of history, 2026)
The purpose of this article is to illustrate the daily life, legal basis, characteristics, difficulties of detention, and adaptation of prisoners to camp life and the acceptance of Soviet doctrine using the example of German prisoners of war during World War II.The article is written at the interdisciplinary intersection of history, law, and sociology. Thus, the methodological basis of the study is formed by methods from history, law, and sociology. Along with interdisciplinary approaches, retrospective, problem-analytical, chronological, biographical, discursive, prosopographical, and anthropological methods were used to explore the article's topic.Drawing on memoirs of prisoners of war and the works of Western scholars, including German historians, this article examines the life of a prisoner, their perception of camp reality, behavioral changes, the transformation of their value system, intercultural communication, and the prisoner's reintegration into post-war society. The study's novelty lies in its exploration and comparative analysis of the daily life of a prisoner of war as a member of a camp society, based on memoirs and the works of German scholars.The article's research findings reveal the negative impact of historical factors on the lives and legal status of German prisoners of war in Soviet camps, including the direct participation of Germans in military operations on Soviet territory, the division of defeated Germany into two states, and the onset of the Cold War. The reasons for the emergence of a political context in the problems of prisoners of war are revealed. Quantitative statistics are determined, and a prosopographical profile of the prisoner of war is developed.
Keywords: World War II, prisoners of war, prisoner of war camp, Germans, Germany, USSR, repatriation.